Armeno-Aethiopica in the Middle Ages: Geography, Tales of Christianization, Calendars, and Anti-Dyophysite Polemics in the First Millennium - Pogossian, Zaroui (Aethiopica, 2021)
Research for this article had the purpose of exploring medieval Armenian–Ethiopian connections. The investigations revealed three main contexts where Ethiopia and Ethiopians feature in the Armenian sources of the first millennium, without necessarily implying real-life encounters. Firstly, the earliest Armenian texts locate Ethiopia and discuss the genealogy of its people in line with the biblical account of the Diamerismos, as well as notions based on Eusebius of Caesarea’s Chronicle translated into Armenian from Syriac in the fifth century. Each author, then, interpreted this information according to his narrative needs or the purpose of a given composition. The discussion of these sources reveals the circulation of classical and Hellenistic notions on Ethiopia and the Ethiopians in Armenian, too, such as the confusion between Ethiopia, Arabia, and India, as well as anthropological or spiritual features attributed to Ethiopians already by classical authors. Secondly, the article analyses a series of calendrical treatises, starting with one authored by the seventh-century polymath Anania Širakac‘i, that passed on a short tale about a sixth-century gathering of scholars in Alexandria in order to determine the date of the Easter and establish tables for its calculation in the future. An Ethiopian wise man Abdiē was part of this international endeavour too, according to this tradition, and his presence marked Ethiopia as part of the eastern Mediterranean learned world, with its own cultural traditions. Armenian language hemerologia also preserved month names in Gǝʿǝz, reproduced in the Appendix. Thirdly, the article draws attention to a completely new way of viewing Ethiopia in ninth- to eleventh-century Armenian anti-dyophysite (antiByzantine) treatises where the Armenian Church and its doctrines or ritual practices were imagined as part of a vast, non-dyophysite orthodox world that included the Ethiopian Church. Intriguingly, this argumentative technique, formulated in terms that one may call anti-colonial ante litteram, may be traced among Coptic and Syriac polemicists as well, a subject of research that would benefit from further analysis.